2021
DOI: 10.3390/jcm10112382
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Screening of Trisomy 21: Could Oxidative Stress Markers Play a Role?

Abstract: Despite significant progress in trisomy 21 (T21) diagnostic tools, amniocentesis is still used for the confirmation of an abnormal fetal karyotype. Invasive tests carry the potential risk of miscarriage; thus, screening biomarkers are commonly used before undergoing invasive procedures. In our study, we investigated the possible application of oxidative stress markers in the prenatal screening of trisomy 21. The DNA/RNA oxidative stress damage products (OSDPs), advanced glycation end (AGE) products, ischemia-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Concluding, ApoA1 plays a meaningful role in the pathogenesis of ES. A1AT is involved in the protection of neurons and glial cells from oxygen and glucose deprivation [ 55 ]. VDBP is an important component of many biochemical processes, including the transport of vitamin D and its metabolites, ensuring proper homeostasis.…”
Section: Previously Established T13 and T18 Pathogenesis—an Indicator...mentioning
confidence: 99%
See 3 more Smart Citations
“…Concluding, ApoA1 plays a meaningful role in the pathogenesis of ES. A1AT is involved in the protection of neurons and glial cells from oxygen and glucose deprivation [ 55 ]. VDBP is an important component of many biochemical processes, including the transport of vitamin D and its metabolites, ensuring proper homeostasis.…”
Section: Previously Established T13 and T18 Pathogenesis—an Indicator...mentioning
confidence: 99%
“…We strongly believe that comprehensive and extensive research can lead to a better understanding of trisomy-related comorbidities and the corresponding phenotypes [ 95 ]. In the following section, future perspectives are highlighted for T13 and T18 investigations in connection with T21 pathogenesis [ 47 , 55 , 96 , 97 , 98 , 99 , 100 ]. It is worth noting that an in vitro model for the study of trisomies other than T21 has not been reported in the literature.…”
Section: Uncoupling Oxidative Stress From the Pathogenesis Of Trisomi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggest that the decrease in A1AT concentration combined with aggravated inflammation processes and oxidative stress observed in T21 pregnancies may negatively impact multiple comorbidities and the occurrence of fetal malformations. The proposed novel T21 screening markers are characterized in Table 4 [ 101 ].…”
Section: Single-protein Determinationmentioning
confidence: 99%